Donor–Acceptor Fluorophores for Visible-Light-Promoted Organic Synthesis: Photoredox/Ni Dual Catalytic C(sp3)–C(sp2) Cross-Coupling - Luo, Jian; Zhang, Jian (ACS catalysis, 2016)
We describe carbazolyl dicyanobenzene (CDCB)-based donor–acceptor (D–A) fluorophores as a class of cheap, easily accessible, and efficient metal-free photoredox catalysts for organic synthesis. By changing the number and position of carbazolyl and cyano groups on the center benzene ring, CDCBs with a wide range of photoredox potentials are obtained to effectively drive the energetically demanding C(sp3)–C(sp2) cross-coupling of carboxylic acids and alkyltrifluoroborates with aryl halides via a photoredox/Ni dual catalysis mechanism. This work validates the utility of D–A fluorophores in guiding the rational design of metal-free photoredox catalysts for visible-light-promoted organic synthesis.